1997
DOI: 10.1097/00007632-199707010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar-Hip Flexion Motion

Abstract: When assessing the relative motion of the lumbar spine and hips in standing forward flexion, there was measurable difference between asymptomatic men and a group of chronic low back pain patients. In particular, two subgroups of individuals with chronic low back pain appeared; one moved relatively similarly to the asymptomatic group, whereas the other sub-group demonstrated reduced hip mobility. These findings indicate the importance of assessing the lumbar and hip flexion motion in chronic low back pain patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 12 publications
2
29
1
Order By: Relevance
“…Included studies were grouped in categories: lordosis [31,32,38,47-49,57,58], range of movement (ROM) [29,30,34,37-42,44,47,50-54,56-59,69,71], relative hip and lumbar contribution to trunk flexion/extension [34,40,50,52,61,71], pelvic angle/relative position and ROM [31,32,57,58], speed/acceleration of lumbar movement [28,34,37,39,41,42,50,71], and proprioception (repositioning accuracy) [33,35,45,46,53,55,60-68,70,72]. Additional file 4 summarises the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies were grouped in categories: lordosis [31,32,38,47-49,57,58], range of movement (ROM) [29,30,34,37-42,44,47,50-54,56-59,69,71], relative hip and lumbar contribution to trunk flexion/extension [34,40,50,52,61,71], pelvic angle/relative position and ROM [31,32,57,58], speed/acceleration of lumbar movement [28,34,37,39,41,42,50,71], and proprioception (repositioning accuracy) [33,35,45,46,53,55,60-68,70,72]. Additional file 4 summarises the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies examined the relative lumbar and hip contribution to flexion movements, five [34,50,52,61,71] during forward flexion, and one [40] returning from a fully flexed position. Four of five studies investigating forward flexion found no significant difference between those with and without LBP when comparing lumbar with hip contribution (ratio) to flexion ROM at end range .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in lumbar range of motion and motion velocity have been recognized in individuals with LBP [16]. Also, reduced hip mobility during forward bending has been reported in the literature [17]. LBP subjects demonstrate a decreased magnitude of hip flexion, but not other hip motions implying that an alteration in activity level of the hamstrings may be present in symptomatic subjects [18].…”
Section: Introductionmentioning
confidence: 94%